The third wheel - Kinney, Jeff (New York : Amulet Books, 2012)
A Valentine's Day dance at Greg's middle school has turned his world upside down until an unexpected twist gives Greg a partner for the dance and leaves his best friend Rowley the odd man out.
Keywords: Middle schools -- Juvenile fiction; Humorous fiction